Efektivitas Prenatal Yoga Terhadap Tingkat kecemasan Ibu Hamil Trimester III Di TPMB Hj. A. Nani Nurcahyani Kota Makassar - Nurul Ainul Yaqin Natsir; Afriani Afriani; Maria Sonda; Agustina Ningsi; Sitti Mukarramah (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
The causes of anxiety in pregnant women, especially in the third trimester, are fear of death, feelings of guilt, fear that the baby will be born with defects, pain, anxiety, preparation for becoming parents, family finances, and the birth process due to previous bad birth experiences. The level of anxiety in third trimester pregnant women can be minimized by doing prenatal yoga. The aim of prenatal yoga is to prepare pregnant women physically, mentally and spiritually. The positive effects of prenatal yoga for pregnant women are, reducing stress, anxiety, pain during pregnancy, discomfort, and reducing labor pain. The aim of this research is to determine the effectiveness of prenatal yoga on the anxiety level of pregnant women in the third trimester. The type of research used is pre eksperiment by design one group pretest posttest design. The sampling technique used is purposive sampling. The sample in this study was 34 pregnant women who were physically and mentally healthy. Data analysis carried out in this research was in the form of univariate and bivariate analysis. The research results showed that there was a significant effectiveness of 0.000 < (p=0.05), proving that there was effectiveness between prenatal yoga on the anxiety level of pregnant women in the third trimester. From the results of this research, it can be concluded that there is the effectiveness of prenatal yoga on the anxiety level of pregnant women in the third trimester at TPMB Hj. A. Nani Nurcahyani.  Keywords : Anxiety; Prenatal gentle yoga; Pregnant women